2021
DOI: 10.1037/pst0000396
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic factors in nature-based therapies: Unraveling the therapeutic benefits of integrating nature in psychotherapy.

Abstract: The psychological benefits of human connection to nature have instigated the development of nature-based therapies (NBTs). This article focuses on the distinct therapeutic factors that characterize NBTs, from the perspective of practitioners from various NBTs, shedding light on the therapeutic value of psychotherapy conducted in the natural environment. To gain a general understanding of the distinct therapeutic factors, currently lacking in the broad field of NBTs, grounded theory methodology was applied. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Various reasons may lead to this phenomenon. First, natural environments provide a space of peace and restoration where inmates can engage in emotional regulation ( Naor and Mayseless, 2021 ) and evoke feelings of happiness, satisfaction, and well-being; these are important factors that influence inmates’ sense of meaning in life. Second, nature exposure can make individuals feel connected with nature ( Richardson et al, 2016 ), prompting them to engage in deep thinking, including reflection on personal behavior and goals ( Kaplan, 1995 ; Herzog et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various reasons may lead to this phenomenon. First, natural environments provide a space of peace and restoration where inmates can engage in emotional regulation ( Naor and Mayseless, 2021 ) and evoke feelings of happiness, satisfaction, and well-being; these are important factors that influence inmates’ sense of meaning in life. Second, nature exposure can make individuals feel connected with nature ( Richardson et al, 2016 ), prompting them to engage in deep thinking, including reflection on personal behavior and goals ( Kaplan, 1995 ; Herzog et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given this effect on attention-related processes, nature exposure has been described as a form of effortless attention training (Tang et al, 2022), and programs have been developed to increase attention, trait mindfulness, and overall well-being via exposure to natural environments (e.g., Card & Burke, 2021;McCormack, 2018). Research has identified that the cognitive process of becoming increasingly aware of and attentive to aspects of the natural environment is a core therapeutic mechanism of these programs (Naor & Mayseless, 2021a, 2021b.…”
Section: Nature Exposurementioning
confidence: 99%
“…Where anxiety is brought about by chronic physical illness, such as cancer, VR therapy can construct positive virtual environments. MIND (2021) note that "spending time in green space or bringing nature into your everyday life can benefit both your mental and physical wellbeing" (Naor and Mayseless, 2021). It is within this context that Wilson and Scorsone explored the benefits of bringing people closer to nature through immersive VR therapy and inducing positive emotions and reducing pain levels.…”
Section: Efficacy Of Virtual-reality Therapymentioning
confidence: 99%